Application of geographic information systems and spatial autocorrelation techniques to analyze industrial employment demand in Costa Rica’s 81 cantons in 2011 - Arias Ramírez, Rafael (2014)
This article is aimed to show high concentration of industrial employment in some geographic areas of Costa Rica. In order to do that we use a very new and complete data set from the Census of Population and Housing of the year 2011, which allows us to create an origin-destination matrix of employment and to have, for the first time in the country, information on industrial employment generated by every county. The use of the spatial dependency index technique, the geographic information system and the coefficient of industrial localization allowed us to demonstrate the existence of strong correlation between industrial employment and the concentration of industrial activities at the county level.